If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6 + -2(2w + -1) = 13w + -2(13 + w) Reorder the terms: 6 + -2(-1 + 2w) = 13w + -2(13 + w) 6 + (-1 * -2 + 2w * -2) = 13w + -2(13 + w) 6 + (2 + -4w) = 13w + -2(13 + w) Combine like terms: 6 + 2 = 8 8 + -4w = 13w + -2(13 + w) 8 + -4w = 13w + (13 * -2 + w * -2) 8 + -4w = 13w + (-26 + -2w) Reorder the terms: 8 + -4w = -26 + 13w + -2w Combine like terms: 13w + -2w = 11w 8 + -4w = -26 + 11w Solving 8 + -4w = -26 + 11w Solving for variable 'w'. Move all terms containing w to the left, all other terms to the right. Add '-11w' to each side of the equation. 8 + -4w + -11w = -26 + 11w + -11w Combine like terms: -4w + -11w = -15w 8 + -15w = -26 + 11w + -11w Combine like terms: 11w + -11w = 0 8 + -15w = -26 + 0 8 + -15w = -26 Add '-8' to each side of the equation. 8 + -8 + -15w = -26 + -8 Combine like terms: 8 + -8 = 0 0 + -15w = -26 + -8 -15w = -26 + -8 Combine like terms: -26 + -8 = -34 -15w = -34 Divide each side by '-15'. w = 2.266666667 Simplifying w = 2.266666667
| x-2(-6.5)=4 | | 0.14(y-7)+0.20y=0.06y-2.8 | | -2(5+6m)+16=p-90 | | a/b1cd | | -112=4(4x+4) | | 3.7+10m=7.18 | | 2(x+1)-3x=6 | | 5(x+4)=7(x-7)+10 | | 55=18x+y | | H=7/6(a-9) | | -105=3(5b+5) | | 7x-2x+2=x-4+6 | | A=7/6(h-9) | | -8/10-4/5 | | 4w^2-5w-4w^2+20w=w-5 | | -3(7x+5)=132 | | X-3/3/4=1/18 | | 4w^2-5w-4w^2+20w=w-4 | | -30x=78 | | 96=4(4b-4) | | 7/3=84/x | | -28-7k=5(-5k-2) | | x+6y=1fory | | X-2/1/4=1/18 | | B+2x=cx | | -15=8v+7v | | 5x-2y=-2a | | X-2/1/4 | | 14x(3+7)=46 | | -5y+3y+10=36 | | 21x^2+6+33x=0 | | -8p-32=-4(6p-4) |